n. 9n=3(nP2)
=>9n^2=3(n!/(n-2)!)
=>9n^2=3(n*(n-1)(n-2)!/(n-2)!)
=>9n^2=3(n*(n-1))
=>9n^2=3(n^2-n)
=>9n^2=3n^2-3n
=>6n^2-3n=0
=>3n(n-2)=0
=>n=0 and n=2
How do i solve algebraically for n. 9n=3(nP2)
5 answers
Did you understand harley?
Yes, i just didn't know how to start with the 9n, thank you!
oops,I made a mistake
6n^2+3n=0
=> 3n(2n+1)=0
=>n= 0 and n= -1/2
6n^2+3n=0
=> 3n(2n+1)=0
=>n= 0 and n= -1/2
The mistake was in starting with 9n and the saying 9n^2.
9n=3(nP2)
=>9n=3(n*(n-1))
=>9n=3n^2-3n
=>3n^2-12n = 0
=> 3n(n-4) = 0
=> n = 0,4
9n=3(nP2)
=>9n=3(n*(n-1))
=>9n=3n^2-3n
=>3n^2-12n = 0
=> 3n(n-4) = 0
=> n = 0,4